PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN NUMERASI SISWA KELAS IV SDN KALICARI 02 SEMARANG - Najma; Khusnul Fajriyah; Diana Endah Handayani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effect of the Problem Based Learning (PBL) model on the numeracy skills of fourth-grade students at SDN Kalicari 02 Semarang. The background of the research is the students' difficulty in applying mathematical concepts in real life due to conventional learning methods. This research used a quantitative approach with a one group pretest-posttest design. The subject consisted of 27 students. Data were collected through tests, observation, and interviews. The results of the Paired Sample T-Test showed a significance value of 0.000 < 0.05, indicating a significant difference between pretest and posttest. The average score increased from 62.96 to 89.44. In addition, 56% of students were categorized as active and 26% as very active during the learning process. These results suggest that the PBL model significantly improves students' numeracy skills and learning engagement.